1987
DOI: 10.1002/jcu.1870150711
|View full text |Cite
|
Sign up to set email alerts
|

Kawasaki syndrome: Cerebral and cardiovascular complications

Abstract: Kawasaki syndrome (KS) is an acute, febrile illness affecting infants and young children predominantly.' It is characterized by fever, lymphadenitis, mucosal and cutaneous inflammation, and vasculitis.2 Cardiovascular complications are common, reported in up to 55% of patient^.^ Fatalities have been reported in 1-2% of patients. Complications include coronary artery aneurysms, myocardial infarction, cerebral infarction, and widespread aneurysmal disease. A case of KS with coronary and iliac artery aneurysms an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…In previously published cases, cerebral infarction was either attributed to (1) inflammatory stenosis or occlusion of cervical or intracranial large‐sized vessels, or (2) thromboembolism from hypokinetic myocardium. Thus, classic parenchymal territories corresponding to the arteries of the circle of Willis and internal carotid arteries were involved 6–8 . Autopsies of children with Kawasaki disease revealed cerebral vasculitis affecting medium‐ and small‐sized vessels, with endoarteritis, periarteritis, and perivascular cuffing 4,9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previously published cases, cerebral infarction was either attributed to (1) inflammatory stenosis or occlusion of cervical or intracranial large‐sized vessels, or (2) thromboembolism from hypokinetic myocardium. Thus, classic parenchymal territories corresponding to the arteries of the circle of Willis and internal carotid arteries were involved 6–8 . Autopsies of children with Kawasaki disease revealed cerebral vasculitis affecting medium‐ and small‐sized vessels, with endoarteritis, periarteritis, and perivascular cuffing 4,9 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, classic parenchymal territories corresponding to the arteries of the circle of Willis and internal carotid arteries were involved. [6][7][8] Autopsies of children with Kawasaki disease revealed cerebral vasculitis affecting medium-and small-sized vessels, with endoarteritis, periarteritis, and perivascular cuffing. 4,9 Moreover, as a single-photon emission computed tomography study showed, asymptomatic focal hypoperfusion areas in 29% of patients with Kawasaki disease, similar to other inflammatory conditions, suggests a vasculitis mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Both generalized 3,7 and localized [7][8][9][10][11][12][13][14][15] CNS symptoms have been reported in Kawasaki disease. Autopsy findings have shown varying degrees of inflammatory changes in brain vasculature, which are usually less extensive than coronary artery involvement.…”
Section: Cognitive Academic and Behavioral Outcomesmentioning
confidence: 99%
“…Histopathology on autopsy of some patients with KD indicated cerebrovascular changes, such as endoarteritis, periarteritis, perivascular cuffing, and the focal necrotizing vasculitis . Several cases have been reported of coronary artery aneurysm with stroke, and imaging showed systemic vasculopathy or aneurysm involving the cerebral artery . In the present case, the patient had coronary artery aneurysm with cerebral artery stenosis.…”
Section: Discussionmentioning
confidence: 49%
“…8 Several cases have been reported of coronary artery aneurysm with stroke, and imaging showed systemic vasculopathy or aneurysm involving the cerebral artery. 9,10 In the present case, the patient had coronary artery aneurysm with cerebral artery stenosis. One could argue whether these two findings were part of the same disease process or were caused by two different diseases, but we consider that KD was the cause of these vascular abnormalities.…”
Section: Discussionmentioning
confidence: 55%